Antecedents of Board Involvement in Overseas Chinese Firms - Lim, B.; Ke, Jun (International Journal of Business and Management, 2015)
The paper examines two prominent theories of strategic behavior that originated within western societies; the institutional and strategic choice theories to describe and explain board involvement in the strategic decision - making process in privately incorporated Chinese firms. These theories have been used extensively by researchers researching in the ‘western” environment of public listed companies, but little conclusive evidence exists regards the issues of board involvement and management practices of privately incorporated Chinese firms. It also looks at the intersection of these theories and Chinese cultural values to provide a rich picture of board behavior in these firms. Its richness are apparent at macro level, examining the relationship between Chinese characteristics and organization structure, and at the micro level for investigating the similarities and differences in attitude of board members with given characteristics. The cultural perspectives at both micro and macro levels able to offer complementary views of Chinese board behavior. The importance of this study is to provide an initial step to help to conceptualize the complexity of board involvement in privately incorporated Chinese firms.